2021
DOI: 10.3390/brainsci11111457
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Response of Limited Brain Metastatic Disease to Focal Hypofractionated Radiation Therapy

Abstract: Background: This is a retrospective study aimed at assessing the volumetric response, morbidity and failure rates of hypofractionated radiation therapy (HFRT) for definitive focal management of limited brain metastasis. Methods: Patients managed with HFRT for unresected limited metastatic (≤10 lesions) brain disease were entered into an ethics-approved database. Included patients had been deemed unsuitable for surgical resection, and lesions managed with prior radiation therapy were excluded. HFRT was delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…Thus, it is as if the GBM MV is larger and associated with two adjacent coronas, BAT and beyond aCCV, whereas metastasis has smaller MV and is surrounded by relatively similar BAT and aCCV volumes. The wider volumetric extension and larger volumes in GBM, relative to metastasis, is consistent with sparse data [30][31][32]. We also found that proton-diffusion features were common to GBM and metastasis: the mean-ADC value decreases, centripetally, progressively from MV to aCCV, and conversely for the mean-FA value, altogether with the centripetal lowering of lesioning processes.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, it is as if the GBM MV is larger and associated with two adjacent coronas, BAT and beyond aCCV, whereas metastasis has smaller MV and is surrounded by relatively similar BAT and aCCV volumes. The wider volumetric extension and larger volumes in GBM, relative to metastasis, is consistent with sparse data [30][31][32]. We also found that proton-diffusion features were common to GBM and metastasis: the mean-ADC value decreases, centripetally, progressively from MV to aCCV, and conversely for the mean-FA value, altogether with the centripetal lowering of lesioning processes.…”
Section: Discussionsupporting
confidence: 87%